Analisis Faktor yang Berhubungan Dengan Produktifitas Kerja di Bagian Produksi Pelintingan PT. Djagung Padi Mas Kota Malang - Safitri, Anastasia Rozalia Sigit; Jenrivo , Fresvian; Basri , Ani Asriani; Arganata, Fariz Zuvil (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
The production results produced by PT Djagung Padi Mas were not in accordance with the planned results, namely in July, June and September the actual production results were less than the production plan results. Appropriate production results will help the company to meet market needs and improve the company's economy. The aim of this research is to determine the relationship between work motivation, work discipline and work nutrition with work productivity and to understand the picture of work motivation, work discipline, work nutrition and work productivity at PT. Djagung Padi Mas. The research method used was quantitative with a total sampling technique on 49 workers using logistic regression analysis tests, with interviews, observations, questionnaire instruments, and the SPSS method. Based on analysis using the SPSS method, the statistical output results show that the significance value of the relationship between work motivation and productivity is sig. 0.098 (sig < 0.05). The relationship between work discipline and productivity has a sig value. 0.268 (sig < 0.05). The relationship between occupational nutrition and productivity has a sig value. 0.236 (sig < 0.05). The conclusion is that work motivation, work discipline and work nutrition do not have a significant relationship with work productivity.